2015
DOI: 10.1159/000438580
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Effects of Traditional Chinese Medication Qiliqiangxin on H9C2 Cardiomyocytes

Abstract: Background/Aims: A traditional Chinese medicine, Qiliqiangxin (QLQX) has been identified to perform protective effects on myocardium energy metabolism in mice with acute myocardial infarction, though the effects of QLQX on myocardial mitochondrial biogenesis under physiological condition is still largely elusive. Methods: H9C2 cells were treated with different concentrations of QLQX (0.25, 0.5, and 1.0 μg/mL) from 6 to 48 hours. Oxidative metabolism and glycolysis were measured by oxygen consumption and extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…The PPAR family consists of PPAR-α, PPAR-δ, and PPAR-γ. It has been reported that activation of PPAR-γ prevented lipopolysaccharide-mediated cardiac dysfunction and that PGC-1α was required for QLQX-associated enhancement in cardiomyocyte mitochondrial energy metabolism 26, 27. In our previous study, we also demonstrated that QLQX could improve cardiac function and attenuate cardiac remodeling after AMI by activating PPAR-γ 7.…”
Section: Discussionmentioning
confidence: 55%
“…The PPAR family consists of PPAR-α, PPAR-δ, and PPAR-γ. It has been reported that activation of PPAR-γ prevented lipopolysaccharide-mediated cardiac dysfunction and that PGC-1α was required for QLQX-associated enhancement in cardiomyocyte mitochondrial energy metabolism 26, 27. In our previous study, we also demonstrated that QLQX could improve cardiac function and attenuate cardiac remodeling after AMI by activating PPAR-γ 7.…”
Section: Discussionmentioning
confidence: 55%
“…Protective effects of QL were demonstrated by a multicenter randomized double‐blind clinical study including 512 heart failure patients 19. It was also reported that QL could improve cardiomyocyte metabolism and inhibit cardiomyocyte apoptosis 20, 21, 22, 23. Our previous work found that QL could promote cardiac angiogenesis and up‐regulate HIF‐1α expression in failing heart and hypoxic CMECs via NRG‐1/ErbB‐PI3K/Akt/mTOR pathway, thus promoting cardiac angiogenesis 24, 25.…”
Section: Introductionmentioning
confidence: 96%
“…Recent work has presented that QL is an effective agent in the cardiovascular diseases treatment [9,10]. QL showed the protective effects in the cardiovascular system via reducing myocardial apoptosis and cardiac fibrosis, thus protecting cardiac function.…”
Section: Introductionmentioning
confidence: 99%